Exploring youth radicalisation through the framework of developmental crime prevention: a case study of Ahmad Numan Haider - Cherney, Adrian (Current issues in criminal justice, 2020)
Criminology has provided useful concepts and theories to inform research on radicalisation to violent extremism. In this paper, the framework of developmental crime prevention is used to explain youth pathways to violent extremism. The key developmental concepts of transition points, risk and protective factors and ecological webs are applied to an in-depth case study of a radicalised, young male Muslim in the Australian state of Melbourne, named Ahmad Numan Haider. Numan Haider was 18 years old when, in 2014, he was shot dead by counter-terrorism police. The Haider case is selected because it appears at first to provide a 'least likely' case in which there appeared to be no early childhood indicators of risk. It is highlighted that the benefit of developmental crime prevention is how it provides a dynamic understanding of risk as being compounded or buffered by transition points. This provides useful insights into the radicalisation process. Lessons for our understanding of youth radicalisation and early intervention are highlighted. The paper complements existing scholarship aimed at explaining the growing problem of youth radicalisation and how to prevent it. Limitations with the approach and study are acknowledged.